The Design of Interactive Listening Quiz for Students using Scratch - Ayu Fitrianingsih; Devina Dwi Saskia; Umi Nur Kholisah; Cahyo Hasanudin; Oktha Ika Rahmawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Scratch is a visual programming platform that allows people without advanced programming knowledge to create interactive projects such as games, animations, and quizzes. The purpose of this research is to create an interactive listening quiz design for university students using the scratch website. The method in this research is using SDLC with waterfall model. The results of this study was the design of interactive listening quizzes by applying the SDLC-Waterfall model by involving five stages, namely 1) requirement (Planning), 2) design (design), 3) Implementation (implementation), 4) Verification (operation), and 5) Maintenance (maintenance). The conclusion of this study is that there were five stages in designing interactive listening quizzes for students using the scratch website.